Validity and Reliability of the Student Perception Questionnaire Instrument regarding the Implementation of the Problem-Based Learning Model in High School Physics Learning - Amalia, Annisa Syukri; Desnita, Desnita; Festiyed, Festiyed; Putra, Amali (PILLAR OF PHYSICS EDUCATION, 2024)
The implementation of the problem-based learning model needs to be known through information from students as subjects. This is so that teachers can build students' insight into teaching and learning activities. Measuring students' perceptions about the implementation of the problem-based learning model needs to be developed. In measuring student perceptions, a standardized measuring instrument in the form of a questionnaire is needed. The questionnaire covers several aspects, namely aspects of student learning activities, aspects of objectives, and aspects of benefits which were then developed into 54 statement items. Validity and reliability testing aims to ensure that the questionnaire instrument can be used properly during research. Instrument development consists of 4 stages, namely planning, construction, quantitative evaluation, and validation. The validity test uses product moment correlation, while the reliability test uses Croanbach's alpha. Instrument testing involved 56 respondents. From the test results, 54 items were declared valid, with a calculated correlation value above > 3,102, which means the criteria are valid. Meanwhile, for the reliability test on 54 items, the calculated Croanbach's alpha value was greater than the Croanbach's alpha table, amounting to 0,982 > 0,70, which means the criteria are reliable. Based on the results of validity and reliability tests, it was concluded that the instrument had met the feasibility of measuring student perceptions regarding the implementation of the problem-based learning model in physics learning.